Do countries use foreign aid to buy geopolitical influence? Evidence from donor campaigns for temporary UN Security Council seats - Bernhard Reinsberg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
In recent years, donor countries have increasingly used different aid allocation channels to boost aid effectiveness. One delivery channel that has grown tremendously is "multi-bi aid" - contributions to multilateral organizations earmarked for specific development purposes. This article examines whether donors use multi-bi aid to further their selfish goals - specifically, to garner political support for their ambition to become a temporary member of the UN Security Council. In this context, multi-bi aid is particularly beneficial to countries with limited experience as foreign aid donors; whose governance quality is weak; and which are more internationalized. Using a sample of OECD/DAC donor countries in 1995-2016, time-series cross-section analysis corroborates these arguments. The analysis draws on a new dataset of media reports proxying for donor interest in winning a temporary seat in the UN Security Council and extended data on multi-bi aid flows. The findings demonstrate that multi-bi aid may be a tool for geopolitical influence, with yet unexplored consequences for aid effectiveness.
Keywords: 330; donor interest; earmarked funding; foreign aid; multi-bi aid; UN Security Council